2014
DOI: 10.1007/s12185-014-1690-z
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 inhibitor ML141 enhances G-CSF-induced hematopoietic stem and progenitor cell mobilization

Abstract: G-CSF is the most often used agent in clinical hematopoietic stem and progenitor cell (HSPC) mobilization. However, in about 10 % of patients, G-CSF does not efficiently mobilize HSPC in clinically sufficient amounts. Cdc42 activity is involved in HSPC mobilization. In the present study, we explore the impact of Cdc42 inhibitor ML141 on G-CSF-mediated HSPC mobilization in mice. We found that the use of ML141 alone only triggered modest HSPC mobilization effect in mice. However, combination of G-CSF and ML141 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Key regulators of the actin cytoskeleton CDC42 and RHOA have already been shown to be associated with thrombocytopenia, due to defects in cytoskeleton organization. [37][38][39][40][41] In affected individuals, we found abnormal tubulin organization in proplatelet-forming megakaryocytes and altered actin polymerization in platelets. Rescue experiments with CDC42 lentiviral particles were not able to fully reverse the phenotype, although the cells produced thinner extensions and swellings, which were barely observed in control cells.…”
Section: Discussionmentioning
confidence: 81%
“…Key regulators of the actin cytoskeleton CDC42 and RHOA have already been shown to be associated with thrombocytopenia, due to defects in cytoskeleton organization. [37][38][39][40][41] In affected individuals, we found abnormal tubulin organization in proplatelet-forming megakaryocytes and altered actin polymerization in platelets. Rescue experiments with CDC42 lentiviral particles were not able to fully reverse the phenotype, although the cells produced thinner extensions and swellings, which were barely observed in control cells.…”
Section: Discussionmentioning
confidence: 81%
“…One week after the last injection, mice were then harvested for histology and hemodynamic measurements, similar to hypoxia-treated groups. ML141 (5 mg per kg body weight), a Cdc42 inhibitor, was dissolved in dimethyl sulfoxide (DMSO), and was intraperitoneally injected daily throughout bleomycin administration protocol (Chen et al, 2015 ), in described experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 2 proved useful for combination with colony-stimulation factor (G-CSF) in the mobilization of hematopoietic stem and progenitor cells. [53] Another study identified EHT1864 (3)asaRac1 inhibitor,which effectively reduces Ab peptide levels in models of Alzheimers diesease in vitro (Figure 3a). [54] Further investigation of the mode of action led to the postulate that the compound tightly binds Rac1 with low nanomolar affinity (dissociation constant K d = 40 nm).…”
Section: Interference With Nucleotide Bindingmentioning
confidence: 99%